Evaluation of Ligamentous Injuries of Knee using Magnetic Resonance Imaging (MRI) - Raza Ahmed, Mumraiz Salik Naqshband, Muhammad Ali, Khair Ul Inam, Fahad Wali Shah Khaggah, Muhammad Kashaf Naseer Cheema, Faisal Masood (Pakistan Journal of Medical & Health Sciences, 2024)
Background and Objectives: This research aimed to assess knee injuries, which is essential for determining the appropriate therapeutic intervention and outcomes. In this study, Magnetic Resonance Imaging was employed to examine the frequency and distribution of diverse forms of damage in traumatized knee joints. Material and Methods: Individuals referred from the Department of Orthopedic surgery in the Department of Radiology with suspected ligamentous injuries secondary to trauma after clinical evaluation were included in the study. They underwent Magnetic Resonance Imaging (MRI) of the knee as advised by the referring surgeon. The study spanned from July 2022 to June 2023. This study was conducted to assess the effectiveness of MRI in diagnosing ligamentous knee injuries because of its obvious potential. Results: Out of the total 50 subjects, 35 (70%) were men and 15 (30%) were women. Right knee was involved in 56% of the cases. The most common ligamentous knee injury was observed to be Anterior Cruciate Ligament tear (48%) followed by medial meniscal injury (40%). Only 4 cases (8%) pf posterior cruciate ligament were identified. Magnetic Resonance Imaging (MRI) has demonstrated significant efficacy as a diagnostic tool for identifying injuries of the cruciate ligaments and menisci when compared to arthroscopic methodologies. Conclusion: In terms of identification of the problems of menisci and cruciate ligaments, MRI is having a higher degree of sensitivity, specificity and accuracy and can be used effectively to diagnose derangements of internal soft-tissues of the knee joint including traumatic injuries of intracapsular structures. Keywords: ligamentous knee injuries, Magnetic Resonance Imaging, Arthroscopy.